Efficacy of emicizumab prophylaxis versus factor VIII prophylaxis for treatment of hemophilia A without inhibitors: network meta-analysis and sub-group analyses of the intra-patient comparison of the HAVEN 3 trial. (2nd December 2019) - Reyes, Adriana; Révil, Cédric; Niggli, Markus; Chebon, Sammy; Schlagmüller, Simone; Flacke, Jan-Paul; Zortel, Max; Paz-Priel, Ido; Asikanius, Elina; Hampton, Roger; Mahajan, Anadi; Schmidt, Elvira; et al.
Abstract: Objectives: To compare the efficacy of emicizumab prophylaxis with that of factor VIII (FVIII) prophylaxis in patients with hemophilia A without inhibitors using two approaches: network meta-analyses (NMA) and additional sub-group analyses from the HAVEN 3 trial. Methods: The NMA used data from trials identified using a systematic literature review and compared bleed rates in patients receiving emicizumab prophylaxis and patients receiving FVIII prophylaxis using a Bayesian, random effects generalized linear model with log link Poisson likelihood. Additional sub-groups of the HAVEN 3 trial included here were defined as patients whose dose-taking behavior met either European label or World Federation of Hemophilia guidelines. A negative binomial regression model was used to conduct an intra-patient comparison of bleed rates within the sub-groups, during treatment with FVIII prophylaxis before entering HAVEN 3 and treatment with emicizumab prophylaxis during HAVEN 3. Results: Four studies were included in the base-case NMA. Evidence showed that the total treated bleed rate was lower with emicizumab prophylaxis compared with FVIII prophylaxis (rate ratio [RR] = 0.36 [95% credible interval (CrI) = 0.13–0.95]). Similar associations were observed in sensitivity analyses. The additional HAVEN 3 analyses also showed lower rates of treated bleeds with emicizumab prophylaxis than with FVIII prophylaxis (RRs [95% confidence interval (CI)] = 0.380 [0.186–0.790] and 0.472 [0.258–0.866] in two sub-groups). These results confirm the original HAVEN 3 intra-patient comparison findings. Conclusions: Combined findings from NMA and additional sub-group analyses of HAVEN 3 support the superiority of emicizumab prophylaxis over FVIII prophylaxis in patients with hemophilia A without inhibitors.